2017
DOI: 10.1371/journal.pone.0185614
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance myography detects age-related muscle change in mice

Abstract: Loss of muscle mass and strength represents one of the most significant contributors to impaired function in older adults. Convenient and non-invasive biomarkers are needed that can readily identify and track age-related muscle change. Previous data has suggested electrical impedance myography (EIM) has the potential to serve in this capacity. In this study we investigated how changes in EIM compared with other standard measures of muscle structure and function in aged compared with young mice. A total of 19 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 51 publications
7
35
0
Order By: Relevance
“…In agreement with a previous study that evaluated EIM in a group of live 3‐month‐old and 25‐month‐old C57/B6 mice and showed an increase in both longitudinal and transverse f c in the aged mice, in the present study we found a consistent increase in f c value in the untreated PolG mice, which correlates with the typical premature aging features associated with this model. Moreover, we also found that f c correlated with the differences in myofiber CSA observed in the PolG animals, unlike the previous work, which showed no significant differences in myofiber CSA between the 3‐ and 25‐month‐old groups.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with a previous study that evaluated EIM in a group of live 3‐month‐old and 25‐month‐old C57/B6 mice and showed an increase in both longitudinal and transverse f c in the aged mice, in the present study we found a consistent increase in f c value in the untreated PolG mice, which correlates with the typical premature aging features associated with this model. Moreover, we also found that f c correlated with the differences in myofiber CSA observed in the PolG animals, unlike the previous work, which showed no significant differences in myofiber CSA between the 3‐ and 25‐month‐old groups.…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies have evaluated the technology for this purpose, including two studies in older adults 6,7 and one study in aged mice. 8 These studies have shown alterations in EIM parameters change over time consistent with aging-associated deterioration, and, in the case of the mouse study, correlation with functional measures and muscle mass. Nevertheless, additional measurements to support the value of EIM in this application are needed, especially in helping to explain the intrinsic alterations in EIM data and how they relate to myofiber health as well as whether they are responsive to a therapeutic intervention.…”
Section: T a B L E 1 Summary Of Datamentioning
confidence: 75%
See 2 more Smart Citations
“…17,33 Older age groups appear to experience functional changes, including reductions in strength and endurance, at rates that exceed those of decrements in muscle mass. 17,33 These differing rates of muscle senescence have been attributed to changes in tissue quality, a broadly applied term that includes loss of myofibers, 20 changes in the proportion of Type I and II fibres, 18 alterations in mitochondrial function, [34][35][36] changes in neural innervation, 37 inter-muscular adipose and connective tissue infiltration, 32,38,24,21 and relative increases in extracellular fluid. 21 Sarcopenia is thus a multidimensional condition that includes loss of muscle mass and changes in muscle quality that lead to functional deficits and ultimately to morbidity and mortality.…”
Section: Strength Prediction Modelsmentioning
confidence: 99%